Rapid Identification of Plasma DNA Samples with Increased ctDNA Levels by a Modified FAST-SeqS Approach. (6th January 2020) - Belic, Jelena; Koch, Marina; Ulz, Peter; Auer, Martina; Gerhalter, Teresa; Mohan, Sumitra; Fischereder, Katja; Petru, Edgar; Bauernhofer, Thomas; Geigl, Jochen B; Speicher, Michael R; Heitzer, Ellen
Abstract: BACKGROUND: Recent progress in the analysis of cell-free DNA fragments [cell-free circulating tumor DNA (ctDNA)] now allows monitoring of tumor genomes by noninvasive means. However, previous studies with plasma DNA from patients with cancer demonstrated highly variable allele frequencies of ctDNA. The comprehensive analysis of tumor genomes is greatly facilitated when plasma DNA has increased amounts of ctDNA. Therefore, a fast and cost-effective prescreening method to identify such plasma samples without previous knowledge about alterations in the respective tumor genome could assist in the selection of samples suitable for further extensive qualitative analysis. METHODS: We adapted the recently described Fast Aneuploidy Screening Test-Sequencing System (FAST-SeqS) method, which was originally established as a simple, effective, noninvasive screening method for fetal aneuploidy from maternal blood. RESULTS: We show that our modified FAST-SeqS method (mFAST-SeqS) can be used as a prescreening tool for an estimation of ctDNA percentage. With a combined evaluation of genome-wide and chromosome arm–specific z -scores from dilution series with cell line DNA and by comparisons of plasma-Seq profiles with data from mFAST-SeqS, we established a detection limit of ≥10% mutant alleles. Plasma samples with an mFAST-SeqS z -score >5 showed results that were highly concordant with those of copy number profiles obtained from our previously described plasma-Seq approach. CONCLUSIONS: Advantages of this approach include the speed and cost-effectiveness of the assay and that no prior knowledge about the genetic composition of tumor samples is necessary to identify plasma DNA samples with >10% ctDNA content.